Euphorbia ebracteolata Hayata (Euphorbiaceae): A systematic review of its traditional uses, botany, phytochemistry, pharmacology, toxicology, and quality control. (June 2021) - Yang, Ting; He, Jun; Yan, Yu; Lian, Wen-Wen; Xia, Cong-Yuan; Xu, Jie-Kun; Zhang, Wei-Ku
Abstract: Euphorbia ebracteolata Hayata, as a traditional medicine, is widely distributed in China, Korea and Japan. In China, the dried root of this plant is named 'langdu'. It is traditionally used to treat oedema, skin ulcers, abdominal distension, cough, asthma, tuberculosis swelling and other diseases. Previous studies have found that the chemical constituents of E. ebracteolata are mainly concentrated in terpenoids, acetophenones, and flavonoids. Both extracts and pure compounds from E. ebracteolata were found to possess many pharmacological activities, such as anticancer, anti-inflammatory, antiviral, and antimicrobial effects. In addition, it was reported that E. ebracteolata shows toxicity. To provide inspiration for further in-depth studies on this plant, this review will provide a timely and systematic summary of E. ebracteolata in traditional uses, phytochemistry, pharmacology toxicology, and quality control. Graphical abstract: Image 1 Highlights: The research progress of  E. ebracteolata  in traditional uses, phytochemistry, pharmacology, toxicology, and quality control is comprehensively summarized. The future development direction of  E. ebracteolata is introduced.